Uniform water distribution type contact oxidation device - GUO JIAN; HU GUILAN; ZHANG YUGUO (2014)
The utility model relates to a uniform water distribution type contact oxidation device which comprises a reaction tank body, a water inlet pipe, a main aeration pipeline, a water outlet pipe and an aeration pipeline, wherein a mixing area, a filling area and a clear water area are respectively arranged in the reaction tank body from bottom to top; the bottom of the mixing area is provided with the water inlet pipe; the main aeration pipeline extending downward is arranged at the clear water area; the main aeration pipeline extends downward to the bottom of the mixing area, and the end of the main aeration pipeline is connected with the aeration pipeline which is flatly laid at the bottom of the mixing area; the filling area is internally provided with filler carrying aerobic microorganisms; the clear water area is also provided with the water outlet pipe; the bottom of the mixing area is provided with a water distribution pipe which is flatly laid at the bottom of the mixing area; the water distribution pipe